Family therapy : concepts, process and practice - Carr, Alan, ....- (Chichester : John Wiley, 2012)
Now in its third edition, this highly regarded and well-established textbook includes up-to-date coverage of recent advances in family therapy practice and reviews of latest research, whilst retaining the popular structure and chapter features of previous editions. It presents a unique, integrative approach to the theory and practice of family therapy. Its distinctive style addresses family behaviour patterns, family belief systems and narratives, and broader contextual factors in problem formation and resolution. It shows how the model can be applied to address issues of childhood and adolescence (e.g. conduct problems, drug abuse) and of adulthood (e.g. marital distress, anxiety, depression). Its student-friendly features: chapters begin with a chapter plan and conclude with a summary of key points; theoretical chapters include a glossary of new terms; case studies and further reading suggestions are included throughout
Previous ed.: 2006.
Keywords: Familjeterapi; Family psychotherapy; Gezinstherapie